Liquid silicone rubber composition and application thereof

By using crosslinking agents and catalysts in the liquid silicone rubber composition to delay the curing speed, the problem of liquid silicone rubber forming too fast at high temperatures is solved, and the slow curing and effective sealing effect is achieved in a high-temperature ultra-high salt environment. Suitable for dissection and water regulating operations in high-temperature ultra-high salt reservoirs.

CN119193123AActive Publication Date: 2024-12-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310751148.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-27
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

The existing liquid silicone rubber is formed too quickly at high temperatures, so it cannot penetrate deep into the deep oil reservoir of high-temperature ultra-high salt rock cracks and holes to effectively seal the cracks, and cannot meet the requirements of water regulation and blockage of high-temperature ultra-high salt rock cracks and holes. .

Method used

Provided is a liquid silicone rubber composition, including silicone rubber, crosslinking agent, catalyst and diluent. Through the synergistic action of weak acid catalyst and crosslinking agent, the curing speed is delayed and it can slowly cure under a high temperature and high mineralization environment. Suitable as a plugging agent for water regulating and blocking operations in high-temperature ultra-high salt reservoirs.

Benefits of technology

After being placed in an oven at 150°C for 8 to 20 hours, the liquid silicone rubber composition reaches F level, good fluidity, adjustable density, salt and high temperature resistance, suitable for adjusting high temperature and ultra-high salt reservoirs such as Tahe Oilfield. Water blocking operation, go deep into the reservoir to effectively seal the cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193123A_ABST
    Figure CN119193123A_ABST
Patent Text Reader

Abstract

The invention provides a liquid silicone rubber composition and application thereof. The liquid silicone rubber composition mainly comprises silicone rubber, a cross-linking agent, a catalyst and a diluent, and further comprises a filler. Wherein the catalyst is a weak acid, and the catalyst and the cross-linking agent have a synergistic effect, so that the curing speed of the liquid silicone rubber can be delayed. The liquid silicone rubber composition is good in fluidity, cannot be diluted when encountering water, is adjustable in density from 1.07 g / cm < 3 > to 1.12 g / cm < 3 >, is salt-resistant and high-temperature-resistant, and can be slowly cured in a high-temperature and high-salinity environment; after the liquid silicone rubber composition is mixed with formation water with the salinity of 22,000 mg / L, the liquid silicone rubber composition is placed in an oven at the temperature of 150 DEG C for 8-20 hours, the strength reaches F grade, and the strength reaches F grade after the liquid silicone rubber composition is placed in the oven at the temperature of 150 DEG C for 8-20 hours; the plugging agent is suitable for profile control and water plugging of high-temperature and high-salt rock fracture-cavity oil reservoirs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil reservoir profile control and water plugging, and in particular relates to a liquid silicone rubber composition and application thereof. Background Art

[0002] The Tahe Oilfield is a high-temperature and ultra-high-salt rock fracture-cave reservoir with a burial depth of more than 5000m, a temperature greater than 125°C, and a mineralization of more than 22×10 4 mg / L, the reservoir is mainly composed of large-scale caves and cracks ranging from several meters to tens of meters, and the water volume of the reservoir space is large. During development, the injected water and bottom water quickly break through the cracks, and the water content of the oil well increases significantly, resulting in a rapid decrease in oil production. A high-density delayed curing system that is both resistant to ultra-high temperatures and dilution is urgently needed. Conventional polymer gels have poor anti-dilution performance, are easily hydrolyzed at high temperatures, and have poor plugging effects. Granular plugging agents mainly refer to particles such as fly ash, cement, and rubber. They are prepared into suspensions and injected into the formation to bridge the pores and throats to achieve plugging. Granular plugging agents have the advantages of low price and high plugging strength, but such plugging agents are difficult to bridge in large fracture channels in fracture-cavity reservoirs, and it is difficult to achieve long-distance plugging. In addition to the outstanding high and low temperature resistance, resilience and hydrophobicity of silicone rubber, liquid silicone rubber also has a certain fluidity and is a very potential plugging agent. However, the existing liquid silicone rubber mainly includes two types: room temperature vulcanization type and high temperature curing type. The former cures and forms in a few hours or even days at room temperature, while the latter cures and forms in a few minutes at high temperature. The too fast curing time at high temperature makes it impossible for it to penetrate deep into the high-temperature and ultra-high salt rock fracture-cavern oil reservoirs to seal the cracks when used as a plugging agent, and cannot meet the requirements of profile adjustment and water plugging in high-temperature and ultra-high salt rock fracture-cavern oil reservoirs. Summary of the invention

[0003] In view of the problem that the liquid silicone rubber in the prior art is formed too quickly at high temperature and cannot penetrate deep into the high-temperature and ultra-high salt rock fracture-cavity oil reservoir to effectively seal the cracks, the purpose of the present invention is to provide a liquid silicone rubber plugging agent that delays curing at a high temperature of not less than 130°C and a high mineralization of not less than 220,000 mg / L.

[0004] To achieve the above object, the present invention provides a liquid silicone rubber composition, which includes silicone rubber, a cross-linking agent, a catalyst and a diluent.

[0005] According to a specific embodiment of the present invention, the liquid silicone rubber composition further includes a filler.

[0006] According to a specific embodiment of the present invention, the total mass of the liquid silicone rubber composition is taken as 100 parts by mass, and the liquid silicone rubber composition includes 20 to 50 parts by mass of silicone rubber, 1 to 10 parts by mass of a cross-linking agent, 0 to 30 parts by mass of a filler, 0.1 to 0.5 parts by mass of a catalyst, and the remainder of a diluent;

[0007] Preferably, the liquid silicone rubber composition includes 20 to 50 parts by mass of the silicone rubber, 3 to 8 parts by mass of the crosslinking agent, 10 to 20 parts by mass of the filler, 0.2 to 0.4 parts by mass of the catalyst and 34.8 to 59.7 parts by mass of the diluent.

[0008] According to a specific embodiment of the present invention, the cross-linking agent is selected from at least one of silicate compounds, alkoxysilane compounds, alkylalkoxysilane compounds, alkenylalkoxysilane compounds, phenylalkoxysilane compounds, halogenated alkylalkoxysilane compounds, isocyanate-containing alkoxysilane compounds and polyalkoxypolysiloxane compounds.

[0009] According to a specific embodiment of the present invention, the catalyst is a weak acid.

[0010] According to a specific embodiment of the present invention, the crosslinking agent is selected from at least one of tetraethyl silicate, tetramethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, trimethoxysilane, octyltrimethoxysilane, chloropropyltriethoxysilane, phenyltriethoxysilane, triethoxysilane, vinyltriethoxysilane, octyltriethoxysilane, vinyltriisopropoxysilane, tetraisopropylorthosilicate, isocyanatepropyltriethoxysilane, crosslinking agent MOSO and crosslinking agent EOSO;

[0011] Preferably, the crosslinking agent is selected from at least one of tetraethyl silicate, phenyltrimethoxysilane, crosslinking agent MOSO and crosslinking agent EOSO.

[0012] The crosslinking agent MOSO described in the present invention is polymethoxy polysiloxane.

[0013] The crosslinking agent EOSO described in the present invention is polyethoxy polysiloxane.

[0014] According to a specific embodiment of the present invention, the catalyst is selected from at least one of acetic acid, caproic acid, lauric acid, stearic acid, oleic acid and adipic acid;

[0015] Preferably, the catalyst is selected from at least one of adipic acid, stearic acid and lauric acid;

[0016] and / or

[0017] The silicone rubber is 107 silicone rubber; and / or

[0018] The diluent is dimethyl silicone oil;

[0019] Preferably, the diluent is recycled dimethyl silicone oil;

[0020] Preferably, the viscosity of the 107 silicone rubber at 25° C. is 500 to 5000 mPa.s; and / or

[0021] The viscosity of the dimethyl silicone oil at 25° C. is 50 to 500 mPa.s;

[0022] Preferably, the viscosity of the 107 silicone rubber at 25° C. is 800 to 4500 mPa.s; and / or

[0023] The viscosity of the dimethyl silicone oil at 25° C. is 100 to 400 mPa.s.

[0024] The 107 silicone rubber described in the present invention is polydimethylsiloxane terminated with silanol groups.

[0025] According to a specific embodiment of the present invention, the filler is selected from at least one of calcium carbonate, fly ash, alumina, silica powder, talc, barium sulfate and zinc oxide; and / or

[0026] The average particle size of the filler is 1000 mesh to 3000 mesh;

[0027] Preferably, the filler is selected from at least one of calcium carbonate, barium sulfate, talc and silica powder; and / or

[0028] The average particle size of the filler is 1200 mesh to 3000 mesh.

[0029] According to a specific embodiment of the present invention, the cross-linking agent MOSO or the cross-linking agent EOSO is prepared by the following method:

[0030] A first low-hydrogen silicone oil and vinyl trimethoxy silane are subjected to a first reaction under the action of a first platinum catalyst to obtain the crosslinking agent MOSO; or

[0031] The second low hydrogen silicone oil and vinyl triethoxysilane are subjected to a second reaction under the action of a second platinum catalyst to obtain the crosslinking agent EOSO.

[0032] According to a specific embodiment of the present invention, after the first reaction, unreacted vinyltrimethoxysilane is removed in vacuum to obtain the crosslinking agent MOSO; or

[0033] After the second reaction, unreacted vinyltriethoxysilane is removed in vacuo to obtain the crosslinking agent EOSO.

[0034] According to a specific embodiment of the present invention, the amount of the first low-hydrogen silicone oil is 100 parts by mass, the amount of the vinyltrimethoxysilane is 5 to 30 parts by mass, and the amount of the first platinum catalyst is 0.2 to 0.5 parts by mass; or

[0035] The amount of the second low-hydrogen silicone oil is 100 parts by mass, the amount of the vinyl triethoxysilane is 5 to 30 parts by mass, and the amount of the second platinum catalyst is 0.2 to 0.5 parts by mass;

[0036] Preferably, the amount of the first low-hydrogen silicone oil is 100 parts by mass, the amount of the vinyltrimethoxysilane is 15 to 20 parts by mass, and the amount of the first platinum catalyst is 0.2 to 0.3 parts by mass;

[0037] or

[0038] The amount of the second low-hydrogen silicone oil is 100 parts by mass, the amount of the vinyl triethoxysilane is 15 to 20 parts by mass, and the amount of the second platinum catalyst is 0.2 to 0.3 parts by mass;

[0039] Preferably, the amount of the first low-hydrogen silicone oil is 100 parts by mass, the amount of the vinyltrimethoxysilane is 20 parts by mass, and the amount of the first platinum catalyst is 0.2 parts by mass; or

[0040] The amount of the second low-hydrogen silicone oil used is 100 parts by mass, the amount of the vinyl triethoxysilane used is 15 parts by mass, and the amount of the second platinum catalyst used is 0.3 parts by mass.

[0041] According to a specific embodiment of the present invention, the hydrogen content of the first low hydrogen silicone oil and the second low hydrogen silicone oil is independently 0.1wt% to 0.3wt%; and / or the viscosity is independently 25mPa.s to 50mPa.s; and / or

[0042] The first platinum catalyst and the second platinum catalyst are independently a complex of zero-valent platinum and vinyl silane; and / or

[0043] The effective platinum content of the first platinum catalyst and the second platinum catalyst is independently 4000 ppm;

[0044] Preferably, the hydrogen content of the first low-hydrogen silicone oil and the second hydrogen silicone oil is independently 0.18wt% to 0.2wt%; and / or the viscosity is independently 30mPa.s to 40mPa.s;

[0045] Preferably, the first low-hydrogen silicone oil has a hydrogen content of 0.18 wt%; and / or a viscosity of 30 mPa.s; or

[0046] The second low-hydrogen silicone oil has a hydrogen content of 0.2 wt% and / or a viscosity of 40 mPa.s.

[0047] According to a specific embodiment of the present invention, the conditions of the first reaction and the second reaction are independently stirring at 100° C. to 130° C. for 1 h to 5 h;

[0048] Preferably, the conditions of the first reaction and the second reaction are independently stirring at 100°C to 120°C for 1h to 2h;

[0049] Preferably, the first reaction is carried out under stirring at 100° C. for 2 h; or

[0050] The second reaction was carried out under stirring at 120° C. for 1 h.

[0051] According to a specific embodiment of the present invention, the viscosity of the liquid silicone rubber composition after mixing all the components at room temperature is 500mPa.s to 5000mPa.s; and / or the density is 1.0g / cm 3 Up to 1.3g / cm 3 ;

[0052] Preferably, the viscosity of the liquid silicone rubber composition after mixing all the components at room temperature is 800mPa.s to 3100mPa.s; and / or the density is 1.07g / cm 3 Up to 1.12g / cm 3 .

[0053] According to a specific embodiment of the present invention, the curing temperature of the liquid silicone rubber composition is 130° C. to 160° C.; and / or the curing time is 8 h to 24 h;

[0054] Preferably, the liquid silicone rubber composition is cured at 150° C. for 8 to 20 hours.

[0055] The curing referred to in the present invention means that the gel strength of the liquid silicone rubber composition reaches F grade according to the visual code evaluation method.

[0056] Application of the liquid silicone rubber composition according to the present invention in oil reservoir profile control and water plugging, especially application as a plugging agent in high temperature and high salt rock fracture-cavity oil reservoir profile control and water plugging;

[0057] Preferably, the high temperature is not less than 130° C.; and / or the high salt has a mineralization degree not less than 220,000 mg / L.

[0058] Beneficial effects of the present invention:

[0059] In view of the problem that the liquid silicone rubber in the prior art is formed too quickly at high temperature and cannot penetrate deep into the high-temperature and ultra-high salt rock fracture-cave oil reservoir to effectively seal the cracks, the present invention provides a liquid silicone rubber composition. The liquid silicone rubber composition mainly includes silicone rubber, a cross-linking agent, a catalyst and a diluent, and secondly also includes a filler. Among them, the catalyst is a weak acid, which synergistically enhances with the cross-linking agent to help slow down the curing speed of the liquid silicone rubber. The liquid silicone rubber composition has good fluidity, will not be diluted when exposed to water, and has a density of 1.07 to 1.12 g / cm 3 Adjustable, salt-resistant and high-temperature-resistant, it can slowly solidify in a high-temperature and high-mineralization environment: after the liquid silicone rubber composition is mixed with formation water with a mineralization of 220,000 mg / L, it is placed in an oven at 150°C for 8 to 20 hours, and its strength reaches Class F. It is suitable as a plugging agent for profile control and water plugging operations in high-temperature and ultra-high-salt oil reservoirs such as the Tahe Oilfield, and can effectively plug cracks deep into the oil reservoir. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is the H-NMR spectrum of the cross-linking agent MOSO prepared in Example 3.

[0061] Figure 2 This is the infrared spectrum of the cross-linking agent MOSO prepared in Example 3.

[0062] Figure 3 This is the H-NMR spectrum of the cross-linking agent EOSO prepared in Example 4.

[0063] Figure 4 This is the infrared spectrum of the cross-linking agent EOSO prepared in Example 4.

[0064] Figure 5 This is the H-NMR spectrum of the 107 silicone rubber used in any one of Examples 1 to 4 and Comparative Examples 1 to 3.

[0065] Figure 6 This is the surface attenuated total reflection infrared spectrum of the liquid silicone rubber composition prepared in Example 1 after gelation. DETAILED DESCRIPTION

[0066] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.

[0067] The platinum catalyst used in Example 3 and Example 4 has a CAS number of 68478-92-2 and an effective platinum content of 4000 ppm, and was purchased from Shanghai Myrel Biochemical Technology Co., Ltd.

[0068] Example 1

[0069] Preparation of liquid silicone rubber composition:

[0070] The liquid silicone rubber composition in this embodiment includes 40g 107 silicone rubber (viscosity of 1000mPa.s), 3g tetraethyl silicate, 20g calcium carbonate particles (average particle size of 3000 mesh), 0.2g adipic acid, and 37.8g recycled dimethyl silicone oil (viscosity of 100mPa.s);

[0071] All components of the liquid silicone rubber composition of this embodiment were mixed and dispersed in a high-speed disperser for 1 hour to obtain a liquid silicone rubber having a viscosity of 800 mPa.s and a density of 1.12 g / cm 3 A liquid silicone rubber composition, a liquid silicone rubber plugging agent.

[0072] Example 2

[0073] Preparation of liquid silicone rubber composition:

[0074] The liquid silicone rubber composition in this embodiment includes 50g 107 silicone rubber (viscosity is 2000mPa.s), 5g phenyltrimethoxysilane, 10g barium sulfate particles (average particle size is 2000 mesh), 0.2g stearic acid, and 34.8g recycled dimethyl silicone oil (viscosity is 200mPa.s);

[0075] All components of the liquid silicone rubber composition in this embodiment were mixed evenly using a three-roll mill to obtain a liquid silicone rubber composition having a viscosity of 1600 mPa.s and a density of 1.09 g / cm 3 A liquid silicone rubber composition, a liquid silicone rubber plugging agent.

[0076] Example 3

[0077] Preparation of cross-linking agent MOSO:

[0078] 100 g of low hydrogen silicone oil (hydrogen content 0.18%, viscosity 30 mPa.s), 20 g of vinyl trimethoxy silane and 0.2 g of platinum catalyst (effective platinum content 4000 ppm) were mixed evenly, stirred and reacted at 100° C. for 2 h, and unreacted vinyl trimethoxy silane was removed in vacuo to obtain a crosslinking agent MOSO;

[0079] Preparation of liquid silicone rubber composition:

[0080] The liquid silicone rubber composition in this embodiment includes 30g 107 silicone rubber (viscosity of 800mPa.s), 8g crosslinking agent MOSO, 20g talcum powder (average particle size of 1200 mesh), 0.4g stearic acid, and 41.2g recycled dimethyl silicone oil (viscosity of 400mPa.s);

[0081] All components of the liquid silicone rubber composition of this embodiment were mixed and dispersed in a high-speed disperser for 1 hour to obtain a liquid silicone rubber composition with a viscosity of 2500 mPa.s and a density of 1.10 g / cm 3 A liquid silicone rubber composition, a liquid silicone rubber plugging agent.

[0082] Example 4

[0083] Preparation of cross-linking agent EOSO:

[0084] 100 g of low hydrogen silicone oil (hydrogen content 0.20%, viscosity 40 mPa.s), 15 g of vinyl triethoxysilane and 0.3 g of platinum catalyst (effective platinum content 4000 ppm) were mixed evenly, stirred and reacted at 120° C. for 1 h, and unreacted vinyl triethoxysilane was removed in vacuo to obtain a crosslinking agent EOSO;

[0085] Preparation of liquid silicone rubber composition:

[0086] The liquid silicone rubber composition in this embodiment includes 20g 107 silicone rubber (viscosity of 4500mPa.s), 5g crosslinking agent EOSO, 15g silicon powder (average particle size of 2000 mesh), 0.3g lauric acid, and 59.7g recycled dimethyl silicone oil (viscosity of 100mPa.s);

[0087] All components of the liquid silicone rubber composition of this embodiment were mixed and dispersed in a high-speed disperser for 1 hour to obtain a liquid silicone rubber composition with a viscosity of 3100 mPa.s and a density of 1.07 g / cm 3 A liquid silicone rubber composition, a liquid silicone rubber plugging agent.

[0088] Comparative Example 1

[0089] The tetraethyl silicate in Example 1 was replaced with an equal mass of vinyl trisbutyl ketoxime silane, a crosslinking agent commonly used for room temperature vulcanized silicone rubber, and the rest was the same as Example 1 to obtain a liquid silicone rubber composition, a liquid silicone rubber plugging agent.

[0090] Comparative Example 2

[0091] The adipic acid in Example 1 is replaced with an equal mass of dibutyltin dilaurate, a catalyst commonly used in room temperature vulcanized silicone rubber, and the rest is the same as Example 1 to obtain a liquid silicone rubber composition, a liquid silicone rubber plugging agent.

[0092] Comparative Example 3

[0093] The tetraethyl silicate in Example 1 is replaced by an equal mass of methyltributylidene oxime silane, and the adipic acid is replaced by an equal mass of dibutyltin dilaurate, and the rest is the same as Example 1 to obtain a liquid silicone rubber composition, a liquid silicone rubber plugging agent.

[0094] Structural characterization of crosslinking agent MOSO, crosslinking agent EOSO, 107 silicone rubber and liquid silicone rubber composition after gelation

[0095] (1) Structural characterization of crosslinker MOSO

[0096] Figure 1 This is the H NMR spectrum of the cross-linking agent MOSO prepared in Example 3. The solvent is deuterated chloroform. A signal of hydrogen on the methoxy group appears at a chemical shift of 3.5 ppm, a signal of the methylene connected to silicon appears at a chemical shift of 0.5 ppm, and a peak at 0 to 0.3 ppm is attributed to the signal of methyl hydrogen.

[0097] Figure 2 This is the infrared spectrum of the crosslinking agent MOSO prepared in Example 3. In the figure, 2959 and 2837 cm -1 The methoxymethyl stretching vibration peak appeared at 2901 cm -1 The stretching vibration peak of silicon methyl group appeared at 2152 cm -1 The absorption peak at 1409cm belongs to the vibration absorption peak of residual silicon hydrogen. -1 The bending vibration absorption peak of methylene appeared at 1258cm -1 The bending vibration absorption peak of methyl group appeared at 1000 to 1200 cm -1 The vibration absorption peak of silicon-carbon bond appears at 797cm -1 The vibration absorption peak of silicon-oxygen bond appears at

[0098] pass Figure 1 The H NMR spectrum and Figure 2 The infrared spectrum shown indicates that the cross-linking agent MOSO, i.e., polymethoxy polysiloxane, of the target structure is prepared in Example 3.

[0099] (2) Structural characterization of crosslinker EOSO

[0100] Figure 3 This is the H NMR spectrum of the cross-linking agent EOSO prepared in Example 4. The solvent is deuterated chloroform. The signal of -CH2-hydrogen on the ethoxy group appears at a chemical shift of 3.75 ppm, the signal of -CH3 hydrogen on the ethoxy group appears at a chemical shift of 1.14, the signal of the methylene group connected to silicon appears at a chemical shift of 0.5 ppm, the peak appearing at 0 to 0.3 ppm belongs to the signal of methyl hydrogen, and the peak at a chemical shift of 4.6 ppm belongs to the signal of residual silicon hydrogen.

[0101] Figure 4 This is the infrared spectrum of the cross-linking agent EOSO prepared in Example 4. -1 The stretching vibration peak of ethoxymethyl appeared at 2927 cm -1The ethoxymethylene stretching vibration peak appeared at 2904 cm -1 The stretching vibration peak of silicon methyl group appeared at 2152 cm -1 The absorption peak at 1409cm belongs to the vibration absorption peak of residual silicon hydrogen. -1 The bending vibration absorption peak of methylene appeared at 1261cm -1 The bending vibration absorption peak of methyl group appeared at 1000 to 1200 cm -1 The vibration absorption peak of silicon-carbon bond appeared at 793cm -1 The vibration absorption peak of silicon-oxygen bond appears at

[0102] pass Figure 3 The H NMR spectrum and Figure 4 The infrared spectrum shown indicates that the crosslinking agent EOSO with the target structure, i.e., polyethoxy polysiloxane, is prepared in Example 4.

[0103] (3) Structural characterization of 107 silicone rubber and liquid silicone rubber composition after gelation

[0104] Figure 5 The H NMR spectrum of the 107 silicone rubber used in any one of Examples 1 to 4 and Comparative Examples 1 to 3 of the present invention shows that methyl signals appear at the chemical shift of 0 to 0.2 ppm, indicating that any one of Examples 1 to 4 and Comparative Examples 1 to 3 of the present invention uses 107 silicone rubber.

[0105] Figure 6 This is the surface attenuated total reflection infrared spectrum of the liquid silicone rubber composition (or liquid silicone rubber plugging agent) prepared in Example 1 after gelation. It can be determined that it is a material based on polydimethylsiloxane. Since the amount of cross-linking agent and catalyst is too small, they cannot be reflected in the spectrum.

[0106] Evaluation of Liquid Silicone Rubber Compositions

[0107] The gelling state of the liquid silicone rubber compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 3 under high temperature and high salt conditions (i.e., 150° C. and a mineralization degree of 220,000 mg / L) was observed, and their delayed curing performance at high temperature was evaluated. The specific steps are as follows:

[0108] ⅰ Weigh 100 g of each of the liquid silicone rubber compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 3, and place them in ampoules together with 50 g of formation water with a mineralization of 220,000 mg / L, respectively. After sealing, place them in an oven at 150° C. and start the experiment; within 2 hours after the start of the experiment, observe and record the gelation state of the liquid silicone rubber composition every 0.1 hour; starting from the time when the experiment time reaches 2 hours, observe and record the gelation state of the liquid silicone rubber composition every 2 hours;

[0109] ii. According to the visual code evaluation method of Sydansk et al., which divides the gel strength of the plugging agent (Gel Strength Codes for short GSC) into 10 levels according to the visual inspection results, the time when the gel formation of the liquid silicone rubber composition prepared in Examples 1 to 4 and Comparative Examples 1 to 3 reaches Grade F is determined in combination with Table 1. The specific results are shown in Table 2.

[0110] Table 1. Gel Strength Code Standards

[0111]

[0112] Table 2. Time for liquid silicone rubber composition to reach F grade

[0113] Serial number Time to reach F level / h Example 1 20 Example 2 14 Example 3 8 Example 4 12 Comparative Example 1 2 Comparative Example 2 0.5 Comparative Example 3 0.2

[0114] It can be seen from Table 2 that the liquid silicone rubber compositions prepared in Examples 1 to 4 take 8 to 20 hours to reach F grade gel strength (specifically the high deformation non-flowing gel in Table 1) at a high temperature of 150°C, and the gel time is long enough. Compared with Example 1, Comparative Example 1 replaces the cross-linking agent tetraethyl silicate with an equal mass of vinyl trisbutyl ketoxime silane, that is, uses a cross-linking agent commonly used for room temperature vulcanized silicone rubber outside the scope of the present invention, and the curing time of the liquid silicone rubber composition prepared therefrom is shortened by 90%, specifically 2 hours, which cannot meet the water plugging operation that requires delayed curing under high temperature conditions; Compared with Example 1, Comparative Example 2 replaces adipic acid with an equal mass of dibutyltin dilaurate, that is, uses a catalyst commonly used for room temperature vulcanized silicone rubber outside the scope of the present invention, and the curing time of the liquid silicone rubber composition prepared therefrom is shortened by Compared with Example 1, in Comparative Example 3, the crosslinking agent tetraethyl silicate is replaced by an equal mass of methyl tributylidene oxime silane, and the catalyst adipic acid is replaced by an equal mass of dibutyltin dilaurate. The replaced crosslinking agent and catalyst are both outside the scope of the present invention. The prepared liquid silicone rubber composition has a very short curing time of only 0.2h at 150°C, which is 99% shorter than that in Example 1. It is also not suitable for water plugging operations requiring delayed curing under high temperature conditions. It can be seen that the liquid silicone rubber compositions prepared in Comparative Examples 1 to 3 cannot be used for profile control and water plugging operations in high-temperature and ultra-high-salt oil reservoirs such as the Tahe Oilfield because of their too fast curing speed at high temperature. The above experimental results can prove that the catalyst and the cross-linking agent in the liquid silicone rubber composition provided by the present invention have a synergistic effect in delaying the curing speed of the liquid silicone rubber, so that the liquid silicone rubber composition can be slowly cured under high temperature and ultra-high salt conditions, and the curing time reaches 8 to 20 hours. It is suitable for use as a plugging agent in profile control and water plugging operations in high-temperature and ultra-high salt reservoirs such as the Tahe Oilfield, and can effectively plug cracks deep into the oil reservoir.

[0115] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A liquid silicone rubber composition comprising silicone rubber, a crosslinking agent, a catalyst and a diluent.

2. The liquid silicone rubber composition according to claim 1, characterized in that: The liquid silicone rubber composition further includes a filler.

3. The liquid silicone rubber composition according to claim 2, characterized in that: Taking the total mass of the liquid silicone rubber composition as 100 parts by mass, the liquid silicone rubber composition includes 20 to 50 parts by mass of silicone rubber, 1 to 10 parts by mass of a crosslinking agent, 0 to 30 parts by mass of a filler, 0.1 to 0.5 parts by mass of a catalyst and the remainder of a diluent.

4. The liquid silicone rubber composition according to any one of claims 1 to 3, characterized in that The crosslinking agent is selected from at least one of silicate compounds, alkoxysilane compounds, alkylalkoxysilane compounds, alkenylalkoxysilane compounds, phenylalkoxysilane compounds, halogenated alkylalkoxysilane compounds, isocyanate-containing alkoxysilane compounds and polyalkoxypolysiloxane compounds.

5. The liquid silicone rubber composition according to any one of claims 1 to 4, characterized in that The catalyst is a weak acid.

6. The liquid silicone rubber composition according to any one of claims 1 to 5, characterized in that The crosslinking agent is selected from at least one of tetraethyl silicate, tetramethoxysilane, methyltrimethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, trimethoxysilane, octyltrimethoxysilane, chloropropyltriethoxysilane, phenyltriethoxysilane, triethoxysilane, vinyltriethoxysilane, octyltriethoxysilane, vinyltriisopropoxysilane, tetraisopropyl orthosilicate, isocyanatepropyltriethoxysilane, crosslinking agent MOSO and crosslinking agent EOSO.

7. The liquid silicone rubber composition according to any one of claims 1 to 6, characterized in that The catalyst is selected from at least one of acetic acid, caproic acid, lauric acid, stearic acid, oleic acid and adipic acid; and / or The silicone rubber is 107 silicone rubber; and / or The diluent is dimethyl silicone oil; Preferably, the viscosity of the 107 silicone rubber at 25° C. is 500 to 5000 mPa.s; and / or The viscosity of the dimethyl silicone oil at 25° C. is 50 to 500 mPa.s.

8. The liquid silicone rubber composition according to claim 2, characterized in that: The filler is selected from at least one of calcium carbonate, fly ash, alumina, silica powder, talc, barium sulfate and zinc oxide; and / or The average particle size of the filler is 1000 mesh to 3000 mesh.

9. The liquid silicone rubber composition according to any one of claims 1 to 8, characterized in that: The liquid silicone rubber composition is cured at a temperature of 130° C. to 160° C. and / or for a curing time of 8 h to 24 h.

10. Use of the liquid silicone rubber composition according to any one of claims 1 to 9 in oil reservoir profile control and water plugging, in particular, use as a plugging agent in high-temperature and high-salt rock fracture-cavity oil reservoir profile control and water plugging; Preferably, the high temperature is not less than 130° C.; and / or the high salt has a mineralization degree not less than 220,000 mg / L.

Citation Information

Patent Citations

  • Liquid silicon rubber composition and preparation method thereof

    CN101983989A

  • High-adhesive one-component deoximation type room-temperature vulcanized silicone rubber sealant and preparation method thereof

    CN103937442A

  • Preparation method of reworkable thermal conductive addition silicone rubber with low bonding strength and low splitting strength

    CN109294240A

  • Single-component liquid silicone rubber and preparation method thereof

    CN111171577A

  • Electrically conductive liquid silicone rubber composition and its Manufacturing method

    KR1020100021640A